Large Differences in the Haptophyte Phaeocystis globosa Mitochondrial Genomes Driven by Repeat Amplifications - Song, Huiyin; Chen, Yang; Liu, Feng; Chen, Nansheng (Frontiers in Microbiology, 2021)
The haptophyte Phaeocystis globosa is a well-known species for its pivotal role in global carbon and sulfur cycles and for its capability of forming harmful algal blooms (HABs) with serious ecological consequences. Its mitochondrial genome (mtDNA) sequence has been reported in 2014 but it remains incomplete due to its long repeat sequences. In this study, we constructed the first full-length mtDNA of P. globosa, which was a circular genome with a size of 43,585 bp by applying the PacBio single molecular sequencing method. The mtDNA of this P. globosa strain (CNS00066), which was isolated from the Beibu Gulf, China, encoded 19 protein-coding genes (PCGs), 25 tRNA genes, and two rRNA genes. It contained two large repeat regions of 6.7 kb and ∼14.0 kb in length, respectively. The combined length of these two repeat regions, which were missing from the previous mtDNA assembly, accounted for almost half of the entire mtDNA and represented the longest repeat region among all sequenced haptophyte mtDNAs. In this study, we tested the hypothesis that repeat unit amplification is a driving force for different mtDNA sizes. Comparative analysis of mtDNAs of five additional P. globosa strains (four strains obtained in this study, and one strain previously published) revealed that all six mtDNAs shared identical numbers of genes but with dramatically different repeat regions. A homologous repeat unit was identified but with hugely different numbers of copies in all P. globosa strains. Thus, repeat amplification may represent an important driving force of mtDNA evolution in P. globosa.